2020
DOI: 10.3139/120.111559
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, mechanical and corrosion properties of TIG welded Hastelloy C-276

Abstract: Hastelloy C-276 is a corrosion resistant nickel based solid solution hardened industrial alloy which has superior mechanical and corrosion properties. In this study, Hastelloy C-276 alloy was welded via the GTAW (Gas tungsten arc welding) method using ERNiCrMo-4 filler metal. Tensile, bending and notch impact tests were performed to determine the mechanical properties. The microstructure of the weld metal was investigated by light microscopy (LM), scanning electron microscopy (SEM) and energy dispersive spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The results indicated that the corrosion potential of the fusion zone was comparable to that of Monel 400 and higher than Hastelloy C-276, potentially leading to an increased corrosion rate. This behavior can be attributed to the presence of carbides and oxides in the fusion zone and base alloys, as described by Tümer et al [33]. The SEM images in figure 12 revealed the surface morphologies of Hastelloy C-276, the weld zone, and Monel 400 after the electrochemical properties test.…”
Section: Corrosionsupporting
confidence: 55%
“…The results indicated that the corrosion potential of the fusion zone was comparable to that of Monel 400 and higher than Hastelloy C-276, potentially leading to an increased corrosion rate. This behavior can be attributed to the presence of carbides and oxides in the fusion zone and base alloys, as described by Tümer et al [33]. The SEM images in figure 12 revealed the surface morphologies of Hastelloy C-276, the weld zone, and Monel 400 after the electrochemical properties test.…”
Section: Corrosionsupporting
confidence: 55%